ULUL AZMI DALAM PEMAHAMAN ISLAM PADA NASKAH SERAT KADIS - Nasrun Salim Siregar (UIN Sumatera Utara Medan, 2022)
The culture of a nation is priceless with its many relics,and among these legacies are manuscripts.Fiber kadis (PB. F. 6. I43) is one of the manuscripts in the collection of the Sonobudoyo MuseumYogyakartawhich is evidence of the history of the work of previous scholars, Arabic manuscript that discusses the five main teachings of Islam, namely creed, Shari'a, philosophy of the creed, the pillars of Faith and Islam and the nature of Allah and His messengers. This research is a philological study that uses ancient Arabic manuscripts as the object of study using the basic method. Philological studies are included in the category of library research. This philological study is refined with several text discussions that according to researchers need to be considered and analyzed, as in the text that Prophet Adam includes Ulul Azmi and Ulul Azmi consists of six prophets. Meanwhile, based on content analysis, Ulul Azmi only consists of five prophets.